214. Antimicrobial Usage and Outcomes following Laboratory Suppression of Antimicrobial Susceptibility Results for Pseudomonas aeruginosa in Sputum Cultures. (26th November 2018) - Liew, Kwee Chin; Evans, Oliver; Wales, Erica; Bond, Stuart; Newton, Peter; Miyakis, Spiros
Abstract: Background: Pseudomonas aeruginosa isolates from sputum cultures do not always require treatment, often representing chronic airways colonization. By releasing sputum P. aeruginosa antimicrobial susceptibility results, only after specific phone request by treating doctors, we aimed to reduce the use of ciprofloxacin without compromising clinical outcomes. Methods: From February 26, 2015, antimicrobial susceptibility results for P. aeruginosa in sputum were routinely suppressed except for immunosuppressed, Intensive Care Unit, cystic fibrosis, or bronchiectasis patients. A database search of the Wollongong Hospital Microbiology laboratory information system identified 108 patients with susceptibility results suppressed (February 26, 2015–February 25, 2017), compared with 108 patients where antimicrobial susceptibility results were routinely reported (February 26, 2013–February 25, 2015). Data collected included age, sex, residency, admission date and diagnosis, comorbidities, allergy, empirical and definitive antibiotic treatment, date of sputum culture, resistance patterns of P. aeruginosa, ciprofloxacin usage, antimicrobial stewardship interventions, length of stay, inpatient mortality, and readmission within 30 days. Results: The prevalence of P. aeruginosa in sputum cultures was 11% (1, 252/11, 388). Patient characteristics were comparable in the two groups. Ciprofloxacin use was significantly reduced postintervention [26.9% (29/108) vs. 39.8% (43/108); P = 0.043] as well as Guidance MS approvals [9.03% (87/963) vs. 17.72% (188/1, 061); P = 0.000001]. Interrupted time series analysis of this intervention was not associated with a significant change in the rates of ciprofloxacin use. Rates of ciprofloxacin resistance were lower postintervention [2.8% (3/108) vs. 16.7% (18/108); P = 0.0006], reaffirmed by SQL database search of the OMNI-Client [9.30% (32/343) vs. 15.00% (60/399); P = 0.0187]. Ciprofloxacin usage against resistance over time There was no difference in length of stay, 30-day readmission, and mortality. Conclusion: This study offers a successful model of collaboration between the microbiology laboratory and antimicrobial stewardship activity. It showed a reduction in the use of ciprofloxacin with possible influence on P. aeruginosa resistance rates, without affecting patient outcomes. Disclosures: All authors: No reported disclosures.